2002
DOI: 10.1161/01.cir.0000032906.33237.1c
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Severe Right Ventricular Failure After Implantable Left Ventricular Assist Device Insertion: Analysis of 245 Patients

Abstract: Background Insertion of an implantable left ventricular assist device (LVAD) complicated by early right ventricular (RV) failure has a poor prognosis and is largely unpredictable. Prediction of RV failure after LVAD placement would lead to more precise patient selection and optimal device selection. Methods and Results We reviewed data from 245 patients (mean age, 54±11 years; 85% male) with 189 HeartMate (77%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(35 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…Finally, we identified an elevated early post-op CVP as independent “modifiable” risk factor for the development of RHF, which has already been described as preoperative risk factor pre-LVAD implantation [ 24 , 25 ]. Moreover, analysis of laboratory parameters showed a significantly higher pre-operative total bilirubin in patients who developed RHF postoperatively, which has also been previously described [ 17 , 26 ]. Thirty days after LVAD implantation, patients who later developed RHF had significantly reduced serum levels of hemoglobin and platelets, and elevated CRP compared to patients without RHF, possibly implicating a higher incidence of bleeding events in these patients, which is in line with the findings of Rame et al [ 21 ], who reported an increased likelihood of gastrointestinal bleeding in patients with late RHF.…”
Section: Discussionsupporting
confidence: 78%
“…Finally, we identified an elevated early post-op CVP as independent “modifiable” risk factor for the development of RHF, which has already been described as preoperative risk factor pre-LVAD implantation [ 24 , 25 ]. Moreover, analysis of laboratory parameters showed a significantly higher pre-operative total bilirubin in patients who developed RHF postoperatively, which has also been previously described [ 17 , 26 ]. Thirty days after LVAD implantation, patients who later developed RHF had significantly reduced serum levels of hemoglobin and platelets, and elevated CRP compared to patients without RHF, possibly implicating a higher incidence of bleeding events in these patients, which is in line with the findings of Rame et al [ 21 ], who reported an increased likelihood of gastrointestinal bleeding in patients with late RHF.…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, high RVSWI in patients undergoing lung transplantation has been associated with poor outcomes [28]. Studies conducted on HFrEF patients have shown that low RVSWI is associated with postoperative RV failure in those under- going LVAD implantation [15,29,30]. In 2 studies, Cesini et al [26] and Kochav et al [23] found that RVSWI was not associated with primary outcomes including LVAD implantation, urgent HT, and death.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated RV stroke work index (RVSWI), defined as work performed by RV each contraction indexed to heart rate and mean arterial pressure, 66 was predictive of RVF when RVSWI < 4. 55,57,60 Additionally, a PAPi < 1.85 has also been shown to be a sensitive predictor of RVF after LVAD implantation. 45,67 To date, the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) criteria stand as the only formally accepted definition of RVF in the setting of LVAD implantation.…”
Section: Defining Right Ventricular Failure After Left Ventricular As...mentioning
confidence: 99%
“…Similarly, the need for inotropic therapy for >14 days 29,35,56,58 is confounded by practice variations across institutions. Various studies have demonstrated RV stroke work index (RVSWI), defined as work performed by RV each contraction indexed to heart rate and mean arterial pressure, 66 was predictive of RVF when RVSWI < 4 55,57,60 . Additionally, a PAPi < 1.85 has also been shown to be a sensitive predictor of RVF after LVAD implantation 45,67 …”
Section: Previous Definitions Of Right Ventricular Failurementioning
confidence: 99%
See 1 more Smart Citation